2010
DOI: 10.1007/s00003-009-0548-4
|View full text |Cite
|
Sign up to set email alerts
|

Survey of dioxins, dioxin-like PCBs and marker PCBs in German feeds of plant origin

Abstract: Within a representative survey the levels of dioxins (PCDD/PCDF), dioxin-like PCBs and marker PCBs in 206 German feed samples were analysed in the years 2004/2005. The sampling plan included compound feed (N = 115) and roughage and succulent feed (N = 91) and reflected the representative feeding situation in Germany. The median content of WHO-PCB-TEQ in analysed feed samples was 0.017 ng/kg [88% dry matter (d.m.)] and consequently more than a factor of 10 below the action level of 0.35 ng/kg (88% d.m.). A diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Because dioxins and PCBs may enter the food chain through several pathways, the magnitude of contamination differs depending on the frequency of exposure and levels of contaminants in each of these pathways. Earlier studies have shown that roughages in general contain higher levels of dioxins than commercial compound feed [ 57 ]. In Table 2 the contamination routes for different production systems (milk, eggs and meat) are further elaborated.…”
Section: Dioxin and Dl-pcb Contamination Risk In The Milk Eggs And Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Because dioxins and PCBs may enter the food chain through several pathways, the magnitude of contamination differs depending on the frequency of exposure and levels of contaminants in each of these pathways. Earlier studies have shown that roughages in general contain higher levels of dioxins than commercial compound feed [ 57 ]. In Table 2 the contamination routes for different production systems (milk, eggs and meat) are further elaborated.…”
Section: Dioxin and Dl-pcb Contamination Risk In The Milk Eggs And Mmentioning
confidence: 99%
“…Contrary to dairy cattle, dioxins are not excreted through the milk and accumulate in the fat. Furthermore, it was found that meat from calves that relied on milk from suckler cows until slaughter contained higher levels of dioxins and DL-PCBs than that of the animals that were fed with milk replacer [ 57 , 81 ]. This might be a consequence of mobilization of dioxins and DL-PCBs in the cow’s tissues and the transfer into milk fat [ 81 ].…”
Section: Dioxin and Dl-pcb Contamination Risk In The Milk Eggs And Mmentioning
confidence: 99%
“…Contamination of food is the result of contaminated feed and, in particular for wildlife fish, from contaminated waters. Hence, food quality assurance necessitates the control of waters [1][2][3], soil [4], food [5][6][7] and feed [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, based on these data, we intented to determine the daily intake of dioxins and PCBs from food of animal origin. Further data on fish and fishery products as well as on feed have been published recently (Karl and Ruoff 2008;Schwind et al 2010).…”
Section: Introductionmentioning
confidence: 99%